EFFECTIVENESS OF TACTICS FOR SELECTING ARTIFICIAL CROWNS IN PATIENTS WITH ALLERGIC BACKGROUND - Khojimurodov Jamshidbek Eraliyevich (TADQIQOTLAR, 2026)
Abstract. According to official statistics in Uzbekistan, 10–15% of the population (depending on the region) suffers from allergic diseases. Studies on the incidence and prevalence of allergic diseases in different countries indicate that these conditions currently affect 20–40% of the population.